THE INFLUENCE OF DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Prasetyo Kurniawan; Surya Budiman; Agus Suhartono; Jaenudin Jaenudin (International Journal Management and Economic, 2023)
This research explores the influence of discipline and work motivation on employee performance at the Technical Education and Religious Training Center (Pusdiklat) under the Ministry of Religious Affairs of the Republic of Indonesia in South Tangerang. A total of 63 respondents were selected using saturation sampling. Data analysis was conducted using SPSS software version 26, employing a quantitative research method and various statistical analysis techniques. The research findings indicate that discipline (X1) positively and significantly impacts employee performance (Y). The motivation variable (X2) also positively and significantly impacts employee performance (Y). The coefficient of determination indicates that the discipline and motivation variables can explain 36.6% of the variation in employee performance. In comparison, the remaining 63.4% is influenced by other factors outside the scope of this research model. The hypothesis test shows that the F-value (17.346) > F-table (3.150) indicates a significant overall influence of discipline and motivation variables on employee performance. This study contributes to a better understanding of the factors that can enhance employee performance in the Technical Education and Religious Training Center environment.